Standardization and validation of Dot-ELISA assay for Paracoccidioides brasiliensis antibody detection - Kamikawa, Camila Mika; Mendes, Rinaldo Poncio [UNESP]; Vicentini, Adriana Pardini (Springer Nature, 2017)
Background: Paracoccidioidomycosis (PCM) is a neglected systemic mycosis caused by a dimorphic fungus of the Paracoccidioides genus. The standard diagnosis is based on isolation of the fungi in culture, and by microscopic visualization of characteristic multiple budding yeast cells in biological samples. However, in some situations, access to the site of injury prevents the collection of biological material. A variety of immuno-serological techniques has proven useful for allowing inferring diagnosis with a certain degree of certainty, thus optimizing time. The aim of this study was to standardize and validate the Dot-ELISA (DE) assay, comparing it with the serological standard, double immunodiffusion (DI). Methods: In order to standardize the DE assay, 143 serum samples were used. Out of those, 23 were from apparently healthy patients, 77 were from patients with confirmed PCM and 43 were from patients with other lung infections (tuberculosis, aspergillosis and histoplasmosis). To validate the DE technique, 300 serum samples from patients with PCM clinical suspicion (probable and possible cases) were employed, and these results were compared with those of DI. Results: The DE assay showed sensitivity of 91%, specificity of 95.4%, positive predictive value of 96%, negative predictive value of 98.2%, accuracy of 93%, and great precision (k = 0.93). In addition, the nitrocellulose membranes have proved to be viable for using at least 90 days after P. brasiliensis B-339 antigen sensitization. Conclusion: Dot-ELISA method was found to be an extremely promising tool as serologic screening technique, because of its high sensitivity. Furthermore, Dot-ELISA shows the prospect of being transferred to laboratories of mycoserology including those with fewer resources or even to be used directly in the field. It has an excellent shelf life - membranes coated with antigen can be used for testing without changes in the pattern of reactivity among laboratories - and presents reliable values of sensitivity, specificity, predictive values, accuracy and a high correlation with the serological standard methodology. Based on the present findings, it possible to state that this technique constitutes a remarkable option to be used in routine diagnosis for public health centers.
Keywords: Dot-ELISA; Immunodiagnostic tool; Paracoccidioides brasiliensis; Paracoccidioidomycosis; Validation